Coastal Heritage and Cultural Resilience (Ethnobiology,, 2018)
This book explores the knowledge, work and life of Pacific coastal populations from the Pacific Northwest to Panama. Center stage in this volume is the knowledge people acquire on coastal and marine ecosystems. Material and aesthetic benefits from interacting with the environment contribute to the ongoing building of coastal cultures. The contributors are particularly interested in how local knowledge -either recently generated or transmitted along generations- interfaces with science, conservation, policy and artistic expression. Their observations exhibit a wide array of outcomes ranging from resource and human exploitation to the magnification of cultural resilience and coastal heritage. The interdisciplinary nature of ethnobiology allows the chapter authors to have a broad range of freedom when examining their subject matter. They build a multifaceted understanding of coastal heritage through the different lenses offered by the humanities, social sciences, oceanography, fisheries and conservation science and, not surprisingly, the arts. Coastal Heritage and Cultural Resilience establishes an intimate bond between coastal communities and the audience in a time when resilience of coastal life needs to be celebrated and fortified.